Hematological parameters and blood biochemical in ten species of marine fish captured by artisanal fishery in Callao Bay, Peru - Sáez, Gloria (2018)
A hematological and blood biochemical evaluation was performed on 10 species of marine fish in the bay of Callao, Peru, in the four seasons of the year and in four sampling areas with different degrees of anthropic disturbance. The species of fish were: «lorna» Sciaena deliciosa (Tschudi, 1846) (Sciaenidae), «lisa» Mugil cephalus Linnaeus, 1758 (Mugilidae), «pejerrey» Odontesthes regia (Humboldt, 1821) (Atherinidae), «pintadilla» Cheilodactylus variegatus Valenciennes, 1833 (Cheilodactylidae), «tramboyo» Labrisomus philippii (Steindachner, 1866) (Labrisomidae), «borrachito» Scartichthys gigas Steindachner, 1876 (Blenniidae), «mojarrilla» Stellifer minor (Tschudi, 1846) (Sciaenidae), «machete» Ethmidium maculatum (Valenciennes, 1847) (Clupeidae), «cavinza» Isacia conceptionis (Cuvier, 1830) (Haemulidae) and «chiri» Stromateus stellatus Cuvier, 1829 (Stromateidae). The values of hematocrit, hemoglobin and triglycerides were significantly higher in E. maculatus, S. minor and I. conceptionis. In S. deliciosa only hemoglobin was higher, and in I. conceptionis only for cholesterol. The leukocyte hematological parameters (lymphocytes, monocytes, basophils, eosinophils and neutrophils) and the HDL showed no variations between species, between seasons or between sampling areas. Hemoglobin and cholesterol were higher for S. deliciosa and hematocrit and cholesterol for M. cephalus and O. regia in the Callao pier area. For M. cephalus higher values of hematocrit, hemoglobin and cholesterol were noted in spring, and cholesterol levels were lower in the summer for M. cephalus and for O. regia.